Thursday

October 23, 2014

October 23, 2014

Posted by **Vanessa** on Tuesday, July 15, 2008 at 12:30pm.

lim (e^x+h-e^h) / h = e^x

h->O =

and explain how this illustrates that ƒ′(x) = ln e • ƒ(x) = ƒ(x)

- Calculus -
**drwls**, Tuesday, July 15, 2008 at 12:39pmThis looks like a Derek question. Please use a single name for your posts

- Calculus -
**Vanessa**, Tuesday, July 15, 2008 at 12:47pmI'm not Derek, I've posted before thanks. We're friends and we take the same class.

- Calculus -

**Answer this Question**

**Related Questions**

Calc. - verify that lim h>0 (e^x+h -e^h)/h=e^x and explain how this ...

Calculus - Find the following limits algebraically or explain why they don’t ...

Calculus - A table of values for f,g,f′, and g′ are given in the ...

Calculus - A table of values for f,g,f′, and g′ are given in the ...

calculus again - Suppose lim x->0 {g(x)-g(0)} / x = 1. It follows necesarily ...

calculus (point me in the right direction please?) - f(x) and f′(x) are ...

calculus - Consider the interval I=[6,7.6]. Break I into four subintervals of ...

calculus - f(x) and f′(x) are continuous, differentiable functions that ...

Urgent Calculus Help - Let H(x)=F(G(x)) and J(x)=F(x)/G(x). Suppose F(7)=4, F&#...

College Physics - Use the relativistic coordinate transformation (x, y, z, t) &#...